Formation of Toxic Oligomeric Assemblies of RNA-binding Protein: Musashi in Alzheimer’s disease - Sengupta, Urmi; Montalbano, Mauro; McAllen, Salome; Minuesa, Gerard; Kharas, Michael; Kayed, Rakez (Acta neuropathologica communications, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disorder associated with structural and functional alterations of brain cells causing progressive deterioration of memory and other cognitive functions. Recent studies demonstrate that several neurodegenerative diseases, including AD exhibit RNA-binding proteins (RBPs) pathologies, including TAR DNA -binding protein (TDP-43), fused in sarcoma (FUS), superoxide dismutase (SOD1) and T-interacting antigen-1 (TIA-1), highlighting the role of RBPs in neurodegeneration. One such group of RBPs, Musashi proteins comprised of MSI1 and MSI2, has been long studied in neurogenesis and cancer biology. Herein, we have investigated the aggregation properties of MSI1 and MSI2 by in vitro assays, their expression and accumulation as well as their possible interactions with other cellular proteins, such as tau in AD pathology. We have performed atomic force microscopy, Western blot, and immunoprecipitation to demonstrate the aggregation properties of recombinant Musashi proteins. Furthermore, we have studied cortical brain sections from AD (N = 4) and age-matched non-demented subjects (N = 4) by Western blot and immunofluorescence microscopy to investigate MSI1 and MSI2 levels and their localization in human brain tissues. Musashi proteins showed in vitro aggregation properties by forming oligomers. We have observed an increase in Musashi proteins levels in AD brain tissues as compared with age-matched non-demented subjects. Moreover, Musashi proteins are observed to form oligomers in the diseased brain tissues. Interestingly, the co-immunofluorescence study has revealed a change in fluorescence pattern of oligomeric Musashi proteins and tau with a high association in the perinuclear area of the cells suggesting changes in function of Musashi proteins. Our data have demonstrated for the first time that MSI1 and MSI2 are present in an oligomeric state in AD brains compared to the age-matched non-demented subjects and that these large assemblies co-localize with tau contributing to the neurodegenerative pathogenesis.